Competitive Intelligence Strategy: Study on Increasing the Superiority of MSME in Palembang City - Gagah Ikhsan Anoraga; Gumilar Rusliwa Somantri; Imam Supriadi (Pusat Publikasi Nusantara, 2023)
BI which is actually technology-based has provided tools and software that can be utilized by every company and MSME to increase competitiveness and business success. However, there are still many MSME players who have not utilized this technology. The purpose of this study is to analyze the stages of competitive intelligence strategies that can increase the competitiveness and success of MSME businesses. Analyze business intelligence implementation strategies in improving the competitiveness and success of MSME businesses. This research uses qualitative methods with a case study approach with SWOT analysis and Porter Theory. The focus of research will be carried out on MSMEs that have superior products in Palembang City, namely Songket and Pempek. The techniques used to collect data are: interviews, observation, and documentation. Data analysis in this study was carried out in 6 stages. The results of this study show that every MSME needs the right strategy that can include market development, or even strategic partnerships to overcome various threats and take advantage of opportunities in the Palembang MSME market by modernizing their business activities. The competitive strategy of MSME development intelligence to increase its competitiveness and business success includes local resources and expanding strong business networks, expanding marketing reach so that products will be better known by consumers, innovation in MSME business models, better decision making through knowledge and understanding of intelligence on data and information can provide excellence, and optimal MSME management such as data collection of all business activities which is more organized and planned. Obstacles and challenges from the implementation of competitive intelligence strategies in increasing the competitiveness and success of MSME businesses in the region, lack of technological knowledge and inability to compete in data utilization are threats that need to be overcome. So that with support from the local government or assistance programs for MSMEs through training, they can overcome these obstacles.